2017
DOI: 10.1177/2158244017712774
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal Differences Among MTurk Workers: Time-Based Sample Variations and Implications for Online Data Collection

Abstract: Background Amazon Mechanical Turk (MTurk) is an online labor market in which people ("requesters") requiring the completion of small tasks ("Human Intelligence Tasks" [HITs]) are matched with people willing to do them ("workers"). MTurk has become a popular data collection tool among social science researchers: In 2015, the 300 most influential social science journals (with impact factors greater than 2.5, according to Thomson-Reuters InCites) published more than 500 articles that relied on MTurk data in full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 50 publications
2
76
0
Order By: Relevance
“…However, it is difficult to assess the impact of these posts without knowing how likely any particular MTurker is to see a post that is relevant to a study they have not yet completed or how discussion frequency in forums compares to the amount of crosstalk among physical lab participants. In one research study about 10% of participants reported finding a study on a site outside of MTurk (Casey et al, 2017), though most forums have strong norms against discussing study content (Chandler, Mueller, & Paolacci 2014). Note that, like most concerns in this chapter, worries about nonnaivete are not unique to only MTurk, as crosstalk has also been observed within college subject pools (Edlund, Sagarin, Skowronski, Johnson, & Kutter, 2009).…”
Section: Solutionsmentioning
confidence: 66%
See 3 more Smart Citations
“…However, it is difficult to assess the impact of these posts without knowing how likely any particular MTurker is to see a post that is relevant to a study they have not yet completed or how discussion frequency in forums compares to the amount of crosstalk among physical lab participants. In one research study about 10% of participants reported finding a study on a site outside of MTurk (Casey et al, 2017), though most forums have strong norms against discussing study content (Chandler, Mueller, & Paolacci 2014). Note that, like most concerns in this chapter, worries about nonnaivete are not unique to only MTurk, as crosstalk has also been observed within college subject pools (Edlund, Sagarin, Skowronski, Johnson, & Kutter, 2009).…”
Section: Solutionsmentioning
confidence: 66%
“…However, averages can be deceiving because experience follows a power law, with a small proportion of extremely active users and a long tail of less active users (Chandler et al, 2014;Rand et al, 2014). Active MTurkers tend to find and complete studies quickly (Casey et al, 2017), leading them to be both very experienced and overrepresented in studies of MTurker knowledge.…”
Section: Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…One limitation of this research is that it is not representative of the entire MTurk population. This is due to workers self-selecting into each study, more experienced workers enrolling more quickly (Arechar, Kraft-Todd, & Rand, 2017;Casey, Chandler, Levine, Proctor, & Strolovitch, 2017), and because I required workers to meet or exceed a minimum "reputation" (i.e., percent of work deemed acceptable by previous requesters), which, to be meaningful, required workers to have completed a minimum number of HITs (Peer, Vosgerau, & Acquisti, 2014). A possible disadvantage of not examining relatively inexperienced workers is that displeasure in recall-based methods may partly be a function of repeated exposure.…”
Section: Limitationsmentioning
confidence: 99%